Rapid nondestructive analysis of threading dislocations in wurtzite materials using the scanning electron microscope. - Naresh-Kumar, G; Hourahine, B; Edwards, P; Day, A; Winkelmann, A; Wilkinson, A; Parbrook, P; England, G; Trager-Cowan, C (2012)
We describe the use of electron channeling contrast imaging in the scanning electron microscope to rapidly and reliably image and identify threading dislocations (TDs) in materials with the wurtzite crystal structure. In electron channeling contrast imaging, vertical TDs are revealed as spots with black-white contrast. We have developed a simple geometric procedure which exploits the differences observed in the direction of this black-white contrast for screw, edge, and mixed dislocations for two electron channeling contrast images acquired from two symmetrically equivalent crystal planes whose g vectors are at 120° to each other. Our approach allows unambiguous identification of all TDs without the need to compare results with dynamical simulations of channeling contrast.